2016
DOI: 10.1016/j.jnutbio.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Green tea catechins and their metabolites in human skin before and after exposure to ultraviolet radiation

Abstract: Dietary flavonoids may protect against sunburn inflammation in skin. Preliminary reports using less complete analysis suggest that certain catechins and their metabolites are found in skin biopsies and blister fluid after consumption of green tea; however, it is not known if they are affected by solar-simulated ultraviolet radiation (UVR) or whether conjugated forms, with consequently altered bioactivity, are present. The present study tested the hypothesis that UVR affects the catechin levels in the skin of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…These results indicate a higher antioxidant content of the skin in the subjects of the tea groups, leading to a faster decrease in the EPR signal of the radical TEMPO. As cutaneous bioavailability studies showed that green tea polyphenols and their metabolites are incorporated into human skin [30,32], the increase in the rate constant might be a result of the direct antioxidant effects of green tea polyphenols in the skin. Polovka et al [55] used EPR spectroscopy to demonstrate that green tea is an effective scavenger of the radicals DPPH (2,2-diphenyl-1-picrylhydrazyl) and 4-hydroxy-TEMPO in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate a higher antioxidant content of the skin in the subjects of the tea groups, leading to a faster decrease in the EPR signal of the radical TEMPO. As cutaneous bioavailability studies showed that green tea polyphenols and their metabolites are incorporated into human skin [30,32], the increase in the rate constant might be a result of the direct antioxidant effects of green tea polyphenols in the skin. Polovka et al [55] used EPR spectroscopy to demonstrate that green tea is an effective scavenger of the radicals DPPH (2,2-diphenyl-1-picrylhydrazyl) and 4-hydroxy-TEMPO in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent study identified 26 green tea metabolites in plasma after oral green tea administration, while 20 metabolites were found in skin blister fluid [30]. In contrast, only 7 substances could be found in skin biopsies, including quercetin and 5-(3′,4′-dihydroxyphenyl)-γ-valerolactone (M6), a ring fission catechin metabolite derived from gut microbiota [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tea polyphenols have attracted considerable attention because of their biologically important activities; such as, anti‐oxidant activity, anti‐carcinogenicity, and anti‐mutagenicity . Daily consumption of green tea has positive impacts on human health . Catechins are the main components of polyphenols in green tea, and the major catechins and their derivatives are as follows: 10–15% (−)‐epigallocatechin gallate (EGCG), 6–10% (−)‐epigallocatechin (EGC), 2–3% (−)‐epicatechin gallate, and 2% (−)‐epicatechin (EC) .…”
Section: Introductionmentioning
confidence: 99%
“…health [4]. Catechins are the main components of polyphenols in green tea, and the major catechins and their derivatives are as follows: 10-15% (−)-epigallocatechin gallate (EGCG), 6-10% (−)-epigallocatechin (EGC), 2-3% (−)-epicatechin gallate, and 2% (−)-epicatechin (EC) [5].…”
Section: Introductionmentioning
confidence: 99%